Ruolo di iASPP nella regolazione del Mismatch repair in melanoma - Senatore, Valentina; Genchi, Giuseppe; Bagetta, Giacinto (My University, 2014)
Cutaneous melanoma is an aggressive malignancy accounting for 4% of skin cancers but 80% of all skin-cancer related deaths. Its incidence is rapidly rising and advanced disease is notoriously treatment-resistant. The role of apoptosis in melanoma pathogenesis and chemoresistance is poorly characterized. Mutations in p53 occur infrequently and are not critical for tumour development. This may alternatively result from p53 upstream or downstream pathway defects or from alterations of p53 family co-activators, including the ASPP family members (Apoptosis Stimulating Proteins of p53). iASPP is the inhibitory member of the ASPP family. By binding p53, iASPP is believed to inhibit apoptosis in cancer, resulting in its oncogenic role. Recently it has been found highly expressed in several types of cancer, such as endometrial and hepatocellular carcinoma, acute leukemia and breast cancer. iASPP upregulation in some cases occurs with a concomitant downregulation of ASPP expression, the pro-apoptotic family member, thus providing a further option for targeting the p53 family in the treatment of cancers. So far, iASPP expression and its role in skin cancer is not yet been explored. Recently great attention has been given to DNA repair processes in melanoma, particularly to Mismatch Repair (MMR). This is a DNA damage repair mechanism, correcting bases mismatches due to replication errors or exogenous agents’ activity, whose defects have been demonstrated leading to genomic instability (microsatellite instability, MSI) frequently linked with cancer. MSI and altered expression of MMR factors such as MSH2 and MLH1 (both at mRNA and protein levels) has often been observed in primary and metastatic melanoma, compared to normal melanocytes and nevi. 8 Aim of this study is to investigate the role of iASPP in melanoma and particularly its involvement in DNA repair and apoptosis. In this work we used RT-PCR and western blot techniques to demonstrate that both MMR factors and iASPP were expressed at higher levels in several melanoma cell lines, mainly metastatic, compared to primary melanocytes extracted from human skin. We also observed a post-translational modification in the MSH2 protein (which is due at least to an ubiquitination) upon increased iASPP expression in three different melanoma cell lines, independently of p53 status. This results in an increase of DNA repair activity measured by MutS(MSH2/MSH6 complex) binding to a DNA bases mismatch. To confirm these results, we used a set of shRNAs targeting iASPP gene in metastatic melanoma cell line WM1158 and we found that the reduction of iASPP leads to a lower MSH2 protein expression, without affecting MLH1, and to a 50% reduction of MutS activity. Immunoprecipitation experiments showed that iASPP directly binds endogenous MSH2 and MLH1 in melanoma cells and this interaction was confirmed by immunostaining where iASPP partially co-localized with MMR factors in the nucleus of melanoma cells. Moreover, iASPP silencing and its consequent reduction in expression and activity of MMR factors, is able to sensitize melanoma cells to apoptosis induced by chemotherapeutic agent cisplatin. Taken together these results confirm the antiapoptotic role of iASPP and suggest a novel role of iASPP in melanoma, such as a modulator of MMR that may help in the future to explain further its oncogenic role in cancer. This study is also the first report available about iASPP expression in melanoma, highlighting the importance of investigating further this important target gene in such a chemoresistant disease. Future studies will be necessary to further elucidate the mechanism by which iASPP interferes with the MMR system and how it affects apoptosis and cell cycle progression in melanoma disease.
Dottorato di Ricerca in Farmacologia e Biochimica della Morte Cellulare, Ciclo XXII, a.a. 2009-2010
Keywords: Farmacologia; Morte della cellula